Practising marbling activity with media and materials in the classroom / Jamaliah Zakaria - Zakaria, Jamaliah (2012)
This research is an Arts-Based Research; conducted using Experimental based study on media and materials that were suitable for marbling activity. As a response to teachers’ reluctance to practice marbling activity due to certain problems, the researcher had delineated four research questions in the hope that the findings from this study could decrease the reluctances. The experimentations with new media and materials, the procedures to be taken during the marbling process and also suggestions of artwork were introduced by the researcher in hoping that it will reduce the problems faced by teachers. By employing the new media, the cleanliness problems that faced by teachers can be avoided. Experiment with new materials also can help new styles of marbling emerged instead of usual styles. The findings of this research can also lead to marbling, a fun and creative activity can be practiced not only in schools, but by public as a common art activity.